2019
DOI: 10.1002/leap.1230
|View full text |Cite
|
Sign up to set email alerts
|

How can a questionable journal be identified: Frameworks and checklists

Abstract: Questionable journals represent an increasing problem in scholarly communication. The warnings about such journals are plentiful, but the methods used to identify them vary a great deal and make it difficult to accurately determine which journals are fraudulent or simply of low quality. This article presents an overview of the existing frameworks for identifying questionable journals and discussions around them. Most of the frameworks rely on describing the journals under investigation according to a set of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
18
0
2
Order By: Relevance
“…The analysis of earlier published evaluation methods, together with our own approach, confirmed that there is a problem with standardization of the evaluation process and that one must not rely merely on compliance with formal criteria when evaluating a journal (Frandsen, ). As further discussion about journal evaluation method is indispensable, it will be useful to carry out a survey among authors regarding their view on what represents good practice in scientific publishing.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The analysis of earlier published evaluation methods, together with our own approach, confirmed that there is a problem with standardization of the evaluation process and that one must not rely merely on compliance with formal criteria when evaluating a journal (Frandsen, ). As further discussion about journal evaluation method is indispensable, it will be useful to carry out a survey among authors regarding their view on what represents good practice in scientific publishing.…”
Section: Resultsmentioning
confidence: 83%
“…This may help detect phenomena that have been overlooked when evaluating journals. It has been confirmed that a close cooperation between authors and librarians is necessary (Frandsen, ), as well as the duty of libraries to continue with raising awareness about untrustworthy journals and helping authors with criteria assessment and detecting possible peculiarities connected with the journal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many have provided suggestions (e.g. Frandsen, 2019), but it remains an open challenge. However, unless the community is able to agree, it is difficult to see how this pernicious practice will be eliminated, which is undermining the scientific process and infecting the scientific archive with papers that have not been subject to high levels of peer review.…”
Section: Discussionmentioning
confidence: 99%
“…When the issue was first raised by Eysenbach (2008), although the term predatory publishing was not used at that time, there has almost certainly been a significant increase. Many authors have provided advice and guidance on how to identify questionable journals, for example, Frandsen (2019).…”
Section: Introductionmentioning
confidence: 99%